Effect of eight weeks of high intensity interval training on AMPK and PGC-1α gene expression levels in the Soleus muscles in rats with myocardial infarction - mehran ghahremani; sara karbalaeifar (فصلنامه ابن سینا)
Background: Myocardial infarction (MI) is the irreversible cell death in parts of myocardium which affects not only cardiovascular system but also other tissues of the body, including skeletal muscle, and in particular the function of mitochondria. It seems that increasing mitochondrial biogenesis is helpful in reducing these complications. Studies have shown that regular exercise increases mitochondrial biogenesis. But its molecular mechanism and the type and intensity of the exercise are not exactly specified. This study intends to examine the effect of eight weeks of high intensity interval training on the gene expression levels of AMPK and PGC-1α in slow-twitch muscles (Soleus) in rats with myocardial infarction. Materials and methods: For this purpose, 12 male Wistar rats with myocardial infarction were divided into two experimental groups (30 minutes regular running, each interval including 4 minutes running with a severity of 90-85% VO2max and two minutes of active recovery with 50%-60% VO2max intensity for three days a week for eight weeks) and control (no exercise). The expression of AMPK and PGC-1α genes was studied as an effective factor in upstream mitochondrial biogenesis. Results: The results showed that the expression of AMPK and PGC-1α genes increased significantly (p<0.001 and p=0.012, respectively). Conclusion: Eight weeks of high intensity interval training increase mitochondrial biogenesis by affecting AMPK and PGC-1α genes in the soleus muscles of rats with myocardial infarction.